2000
DOI: 10.1002/(sici)1097-4628(20000228)75:9<1103::aid-app3>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation and stabilization of styrene-butadiene-styrene rubber

Abstract: Photooxidative degradation and stabilization of a polystyrene-block-polybutadiene-block-polystyrene thermoplastic elastomer using a polychromatic UV light in air at 60°C has been studied by monitoring the appearance of the hydroxyl and carbonyl groups in Fourier transform infrared spectroscopy. The extent of photooxidative degradation in different samples has been compared. The rate of photooxidation was also estimated in the presence of different concentrations of 2,6-di-tert-butyl-4-methylphenol [BHT], 2-(2Ј… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…The surface of the samples turned to yellowish in the initial stage of the weathering tests. With the aging process proceeding, the surface of the sample turned to be more yellow, which was caused by the degradation of the SBS copolymer 12…”
Section: Resultsmentioning
confidence: 99%
“…The surface of the samples turned to yellowish in the initial stage of the weathering tests. With the aging process proceeding, the surface of the sample turned to be more yellow, which was caused by the degradation of the SBS copolymer 12…”
Section: Resultsmentioning
confidence: 99%
“…In styrene-butadiene copolymer, styrene units seems to not play a significant role in photo-oxidation; in fact, there is no change of phenyl ring during irradiation and no "yellowing" was observed. Differently, Allen et al [29,30] found that, in SEBS copolymer, both styrenic and olefinic phases undergo degradation; photo-oxidation of the polystyrene phase leads to the formation of acetophenone chromophores due to end-chain oxidation and scission. Degradation in the styrene phase also yielded the formation of stilbene-type, which can contribute significantly to the strong yellowing observed in the irradiated SEBS.…”
Section: Assessment Of Photo-oxidation Behavior Of Sbsmentioning
confidence: 99%
“…It is generally admitted that the photo-degradation of SB occurs by two simultaneous events: formation of oxidized species, mainly in the polystyrene units, and crosslinking process taking place in the polybutadiene phase. It was reported that the use of a suitable stabilization system, such as piperidinyl-based stabilizer, can prevent the crosslinking process and can, therefore, protect successfully the SB copolymer against photo-degradative phenomena [30]. In this work, the photo-oxidative behavior of polystyrene-blockpolybutadiene-block-polystyrene (SBS) based nanocomposites, particularly SBS/CNTs and SBS/CNTs-COOH nanocomposites was investigated and compared to that of pristine SBS copolymer, in order to probe the effectiveness of CNTs in the protection against UVB induced degradation.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the formation of hydrogen peroxide, alcohol, hydroxyl, acidic, carboxyl and ketonic functional groups during the UV aging process, which increased the polarity of the fragments of the SBS molecular chain. 24 UV aging causes chemical reactions to occur and changes the molecular structure of asphalt. For example, the degradation caused by oxidation reactions between methylene and unsaturated chains leads to the formation of ketones and carboxylic acids.…”
Section: G Afm Images Of Asphalts After the Uv Aging Processmentioning
confidence: 99%